Keaktifan OMK Dalam Bidang Liturgia dan Pewartaan Di Lingkungan ST. Kristoforus, Paroki Perawan Maria dari Gunung Karmel - Skolastika Dinda Ayu Maharani; Intan Sakti Pius X (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
Catholic Young People (OMK) have a crucial role in the Church's mission and are the hope for the future of the Church and society. They are considered the backbone of the Church, tasked with guiding the people and participating in various ecclesiastical tasks and services. The age range for OMK is between 16 and 35 years and requires direction from the Church to fulfill its role as the next generation well. OMK can channel enthusiasm through spiritual activities such as prayer, Eucharist celebrations, and a deep understanding of the faith. In addition, liturgy has an important role in strengthening the relationship with God, while preaching is the main task of the Church to spread Christ's teachings throughout the world. OMK St. Christopher is actively involved in liturgy and preaching, to form the character of young people in the aspects of self-confidence, cooperation, and positive values. This research aims to understand how OMK is involved in spiritual life and why many students from outside the community join OMK Kristoforus. This emphasizes that the responsibility for the cadre formation of the younger generation and the culture of liturgical music is not only the task of the Church but also the collective responsibility of all church members in safeguarding and enriching future generations.